The Science of Sustainability Approach in Halal Tourism Development Based on the Useful Power of the Malay Community in Palembang - Muhammad Amiin Fauzi; Ris'an Rusli; Heri Junaidi; Hilda (Postgraduate, University of Mataram, 2026)
This research investigates the construction of halal tourism development grounded in the sustainability science approach, specifically leveraging the useful power (daya guna) of the Malay community in Palembang, Indonesia. While halal tourism has grown globally, existing models often prioritize commercial metrics over substantive religious values and local cultural wisdom. This study employs a qualitative phenomenological approach to analyze how the Malay community constructs the meaning of